STUDY AND PERFORMANCE OF STRENGTH AND DURABILITY TEST ON CEMENT WITH ADDITION OF CERAMIC WASTE AND MICRO SILICA - Vishwakarma, Dharmesh Kumar; Gupta, Harsh (International Journal of Research -GRANTHAALAYAH, 2021)
In this paper, we are studying about properties of cement and concrete such as strength and durability. Crushed ceramic-based waste and silica instead of sand and cement. In this way, we are performing tests such as Compressive Strength Testing and Durability Test. In this study, the cement fraction is replaced by 5% and 10% with micro-silica and sand from 0%, 15%, 30% and 50% with ceramic waste.